Epigenetic biomarkers in cancer - Brown, Bob (Henry Stewart Talks, 2012)
Epigenetics, levels of control, The patient cancer journey-multiple impact points -Key translational areas for epigenetics, DNA methylation as cancer biomarker, DNA methylation analysis methods, Epigenetic gene silencing in malignant cells, CpG methylation and clinical outcome, Causes of aberrant DNA methylation in cancer, Stem cell targets, EZH2 as a potential anti-cancer target, Epigenetic modification as drug targets, Epigenetic therapies, DNA methylation versus platinum resistance, Phase II trial of Decitabine & Carboplatin, Effects of low doses of DNA-demethylation agents, Epigenetic therapies challenges